Communication between cultures - Samovar, Larry A.; McDaniel, Edwin R.; Porter, Richard E. (Boston, Massachusetts : Cengage Learning, 2017)
Packed with current research and examples, the 9th editions equips students with a deep understanding and appreciation of different cultures while helping them develop practical communication skills. Part I introduces the study of communication and culture; Part II focuses on the ability of culture to shape and modify our view of reality; Part III puts the theory of intercultural communication into practice; and Part IV converts knowledge into action. This is the only text to consistently emphasize religion and history as key variables in intercultural communication. Compelling examples force students to examine their own assumptions, perceptions, and cultural biases--enabling them to
understand the subtle and profound ways culture affects communication. The ninth edition offers expanded discussions of the impact of globalization, a new chapter on intercultural communication competence, and more coverage of new technology.
1. Intercultural communication: a requirement for the interdependent global society -- 2. Communication and culture: the voice and the echo -- 3. The deep structure of culture: lessons from the family -- 4. Worldview: cultural explanations of life and death -- 5. Cultural history: precursor to the present and future -- 6. Cultural values: road maps for behavior -- 7. Culture and identity: situating the individual -- 8. Verbal messages: exchanging ideas through language -- 9. Nonverbal communication: the messages of action, space, time, and silence -- 10. Intercultural communication in contexts: application in business, education, and healthcare -- 11. The challenges of intercultural communication: managing differences
Includes bibliographical references (p. 409-445) and index
Keywords: Communication and culture; Intercultural communication